2008
DOI: 10.1007/s00442-007-0955-0
|View full text |Cite
|
Sign up to set email alerts
|

Germination behaviour of annual plants under changing climatic conditions: separating local and regional environmental effects

Abstract: The role of local adaptation and factors other than climate in determining extinction probabilities of species under climate change has not been yet explicitly studied. Here we performed a field experiment with annual plants growing along a steep climatic gradient in Israel to isolate climatic effects for local trait expression. The focus trait was seed dormancy, for which many theoretical predictions exist regarding climate-driven optimal germination behaviour. We evaluated how germination is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 68 publications
3
54
0
Order By: Relevance
“…A1b) that was removed shortly after the first major rain. Previous experiments indicated that the organza cover neither inhibits germination nor alters the amount of water and light reaching the soil surface (Petru˚and Tielbo¨rger 2008).…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A1b) that was removed shortly after the first major rain. Previous experiments indicated that the organza cover neither inhibits germination nor alters the amount of water and light reaching the soil surface (Petru˚and Tielbo¨rger 2008).…”
Section: Field Experimentsmentioning
confidence: 99%
“…For our experiment, we used four target species that are characterized by a wide distribution range and display ecotypic differentiation with respect to rainfall availability (Petru˚and Tielbo¨rger 2008, Tielbo¨rger et al 2012. We tested the hypotheses that (1) plants perform better under home site conditions, irrespective of biotic interactions; (2) the presence of neighbors reduces plant fitness most under favorable climatic conditions (i.e., wetter climates) because of increased competition; (3) plants from productive environments perform better in away-from-home soil, as opposed to plants from unproductive environments that perform better in home soil; (4) the effect of soil biota in productive soil origins reduces plant performance more than in less productive soil origins.…”
Section: Introductionmentioning
confidence: 99%
“…17 More attention has been paid to the indirect effects of changes in precipitation patterns on grassland seed banks. First, germination in response to soil moisture is species-specific, [20][21][22] with moisture affecting both the percentage and speed of germination 20 or having a weak effect buffered by soil type. 22 Second, changes in rainfall might modify the soil microbial community, which is the primary cause of seed death for some grassland species.…”
Section: Introductionmentioning
confidence: 99%
“…First, germination in response to soil moisture is species-specific, [20][21][22] with moisture affecting both the percentage and speed of germination 20 or having a weak effect buffered by soil type. 22 Second, changes in rainfall might modify the soil microbial community, which is the primary cause of seed death for some grassland species. 23,24 For example, the combination of additional summer rainfall and winter warming had no significant direct effect on seed banks after 2 years, but the seed longevity of some grassland species tested was increased by applying fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…While some role of environmental variation in driving selection for dormancy seems indisputable, empirical tests of the relationship between environmental variability and dormancy rates have yielded mixed results (reviewed in Evans and Dennehy 2005; and see critiques of empirical study to date in Evans et al 2007; see also Petru and Tielborger 2008). Evans and Dennehy (2005) cite Hacker and Ratcliff (1989), Ehrman and Cocks (1996), and Shem-Tov et al (2002) as finding mixed results, and Jain (1982), Gutterman and Edine (1988), and Platenkamp (1991) as finding results contrary to the predicted positive correlation between variance in reproductive success and dormancy.…”
Section: Introductionmentioning
confidence: 99%